Chinese Environmental Contention : Linking Up against Waste Incineration - Bondes, Maria (Amsterdam Amsterdam University Press, 2019)
A plethora of new actors has in recent years entered China$1 (Bs environmental arena. In Western countries, the linkages and diffusion processes between such actors often drive environmental movements. Through a study of Chinese anti-incineration contention, *Chinese Environmental Contention: Linking Up against Waste Incineration* investigates how the different contentious actors in China$1 (Bs green sphere link up, and what this means for environmental contention. It addresses questions such as: What lies behind the notable increase of environmental protests in China? And what are the potentials for the emergence of an environmental movement? The book shows that a complex network of ties has emerged in China$1 (Bs environmental realm under Hu Jintao. Affected communities across the country have connected with each other and with national-level environmentalists, experts and lawyers. Such networked contention fosters both local campaigns and national-level policy advocacy. Beyond China, the detailed case studies shed light on the dynamics behind the diffusion of contention under restrictive political conditions.s
English
Keywords: China; Political activism; Environmentalist, conservationist & Green organizations; Political activism; China; Environmentalists